Mechanisms of ultrasonic modulation of multiply scattered incoherent light based on diffusion theory - 朱莉莉 李晖 (Chinese physics B, 2015)
An analytic equation interpreting the intensity of ultrasound-modulated scattering light is derived, based on diffusion theory and previous explanations of the intensity modulation mechanism. Furthermore, an experiment of ultrasonic modulation of incoherent light in a scattering medium is developed. This analytical model agrees well with experimental results,which confirms the validity of the proposed intensity modulation mechanism. The model supplements the existing research on the ultrasonic modulation mechanism of scattering light.